2022
DOI: 10.3390/ijms23169126
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the Candidate Interacting Proteins of SELF-PRUNING 6A (SP6A) in Solanum tuberosum

Abstract: SELF-PRUNING 6A (SP6A), a homolog of FLOWERING LOCUS T (FT), has been identified as tuberigen in potato. StSP6A is a mobile signal synthesized in leaves and transmitted to the stolon through phloem, and plays multiple roles in the growth and development of potato. However, the global StSP6A protein interaction network in potato remains poorly understood. In this study, BK-StSP6A was firstly used as the bait to investigate the StSP6A interaction network by screening the yeast two-hybrid (Y2H) library of potato,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In other words, BIN2's regulation of hormone signals in the process of potato formation is not unitary but ultimately promotes the expression of key genes in potato tuber formation to promote potato formation. In addition, it has been reported that the interaction between SP6A and SWEET11 can promote its enzyme activity [35]. In this experiment, protein interaction in potatoes was confirmed, and the activity of SWEET protein in StBIN2-overexpressing potatoes was also significantly increased in the predominant tuber-expansion stage, which also promoted potato formation.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In other words, BIN2's regulation of hormone signals in the process of potato formation is not unitary but ultimately promotes the expression of key genes in potato tuber formation to promote potato formation. In addition, it has been reported that the interaction between SP6A and SWEET11 can promote its enzyme activity [35]. In this experiment, protein interaction in potatoes was confirmed, and the activity of SWEET protein in StBIN2-overexpressing potatoes was also significantly increased in the predominant tuber-expansion stage, which also promoted potato formation.…”
Section: Discussionsupporting
confidence: 61%
“…ABI5 and SP6A (a FT family member) interact with each other to regulate potato tuber development [34]. In addition, the sugar transporter SWEET11 potentially interacts with SP6A [35].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis , BRANCHED1 interacts with FT but not TFL1 to prevent floral transition in the axillary meristem [ 129 ], suggesting a conserved regulatory network across plant species. StSP6A was also found to interact with Flowering-Promoting Factor 1, No Flowering in Short Days 1 (StNFL1), and StNFL2, which are likely crucial for tuber formation [ 130 ].…”
Section: Pebp Signaling Network In Underground Storage Organ Formationmentioning
confidence: 99%
“…The yeast two-hybrid (Y2H) system is a valuable tool for swiftly detecting novel protein-protein interactions across various organisms ( Rodriguez-Negrete, Bejarano & Castillo, 2014 ). This approach has been effectively utilized to discover potential interactors for numerous key plant proteins ( Kong et al, 2019 ; Wang et al, 2022 , 2021b , 2021c ). For instance, a Y2H screen using an apple cDNA library identified MdBT2, a nitrate-responsive protein interacting with MdMYB1 and influencing anthocyanin accumulation ( Wang et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%